THE EFFECT OF THE INQUIRY TRAINING MODEL TOWARDS SCIENCE PROCESS SKILLS OF STUDENTS ON PHYSICS LESSON - Abdul Hakim; Aisyah . (Jurnal Pendidikan Fisika, 2016)
This study aimed to know the effect of science process skills of students and activity among the inquiry training and the conventional learning. This research is quasi-experimental study using pre-test and post-test design. The population of the study was students in Medan. Techniques that used to gain a simple is cluster random sampling, the first was grade as experimental class used the inquiry training model and the second was grade as the control class used the conventional learning. The instruments of this study were the science process skills test. The activity, affective, and psychomotor was used observation sheet. The analysis results that the inquiry training was better than that conventional learning in improving the science process skills of students.